Financial Restatement on Manufacture Sector Company Reviewed from The Aspect of Corporate Governance and Company-Specific Characteristics - Fitri Laela Wijayati (Profesional Muda Cendekia Publishing, 2023)
This research was conducted because there was a phenomenon of financial restatement by manufacturing companies listed on the Indonesia Stock Exchange in 2015-2020. This study was conducted with the aim to test whether there was an influence of the independent variable corporate governance and company-specific characteristics on the dependent variable of financial restatement. The population in this study were manufacturing sector companies listed on the Indonesia Stock Exchange for the 2015-2020 research period. The sampling technique used was purposive sampling so that a sample of 42 companies was obtained for 6 years and produced 252 observational data. The data analysis technique used in this research was logistic regression analysis. The results of the study showed that the audit quality variable had a positive effect on financial restatement, while the variable size of the board of commissioners, independent commissioners, audit committee expertise, audit quality, executive compensation, company age, company performance, company leverage and liquidity have no effect on financial restatement.